2010
DOI: 10.1088/0953-8984/22/45/454115
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrical characterization of a pore–cavity–pore device

Abstract: We present a solid state nanopore device structure comprising two nanopores which are stacked above each other and connected via a pyramidal cavity of 10 fl volume. The process of fabrication of the pore-cavity-pore device (PCP) relies on the formation of one pore in a Si(3)N(4) membrane by electron beam lithography, while the other pore is chemically etched into the Si carrier by a feedback controlled process. The dimensions of the two nanopores as well as the cavity can be adjusted independently, which is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…1b shows transmission electron microscope (TEM) images of a typical one. The structure is similar to the pore-cavity-pore device developed by Pedone et al 24 , but it features a cylindrical cavity as opposed to a pyramidal one. Furthermore, we judge our fabrication method to be simpler while granting us better control over the device dimensions.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1b shows transmission electron microscope (TEM) images of a typical one. The structure is similar to the pore-cavity-pore device developed by Pedone et al 24 , but it features a cylindrical cavity as opposed to a pyramidal one. Furthermore, we judge our fabrication method to be simpler while granting us better control over the device dimensions.…”
Section: Resultsmentioning
confidence: 88%
“…Rant et al 24 took an important step towards that goal when they developed devices comprising two pores and a microscale cavity. They demonstrated that the diffusion of particles and DNA can be significantly slowed inside the cavity 25 .…”
mentioning
confidence: 99%
“…6 The latter causes the smaller pores to encounter strictly and tightly flowing electrical double layer on each side of the pore wall which initiates ion movement blockings inside the pore, high resistance in the system leading to signal amplification, 39,40 and low translocation velocity due to intense interaction between DNA and nanoporous surface. 19,20,41 Following up the optimum analytical performance of Au nanoporous EGFET made by 100 nm PS template and 40 nm thick Au film, this substrate was subsequently used for specificity test. The specificity principle may in the future be applied to realizing a multianalyte Au nanoporous biosensor.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Not only that, in biomolecular detection, the potency of metallic nanopores includes an externally controllable electric potential owing to their ability to change flow direction by reversing the polarity of the potential difference between the pore and buffer solution.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation